Mutagenic and carcinogenic potential of a textile azo dye processing plant effluent that impacts a drinking water source - Alves de Lima, Rodrigo Otavio; Bazo, Ana Paula; Salvadori, Daisy Maria Favero [UNESP]; Rech, Celia Maria; Oliveira, Danielle de Palma; Umbuzeiro, Gisela de Aragao (Elsevier B.V., 2007)
Recently a textile azo dye processing plant effluent was identified as one of the sources of mutagenic activity detected in the Cristais River, a drinking water source in Brazil [G.A. Umbuzeiro, D.A. Roubicek, C.M. Rech, M.I.Z. Sato, L.D. Claxton, Investigating the sources of the mutagenic activity found in a river using the Salmonella assay and different water extraction procedures, Chemosphere 54 (2004) 1589-1597]. Besides presenting high mutagenic activity in the Salmonella/microsome assay, the mutagenic nitro-aminoazobenzenes dyes CI Disperse Blue 373, Cl Disperse Violet 93, and CI Disperse Orange 37 [G.A. Umbuzeiro, H.S. Freeman, S.H. Warren, D.P Oliveira, Y. Terao, T. Watanabe, L.D. Claxton, the contribution of azo dyes in the mutagenic activity of the Cristais river, Chemosphere 60 (2005) 55-64] as well as benzidine, a known carcinogenic compound [T.M. Mazzo, A.A. Saczk, G.A. Umbuzeiro, M.V.B. Zanoni, Analysis of aromatic amines in surface waters receiving wastewater from textile industry by liquid chromatographic with eletrochemical detection, Anal. Lett., in press] were found in this effluent. After similar to 6 km from the discharge of this effluent, a drinking water treatment plant treats and distributes the water to a population of approximate 60,000. As shown previously, the mutagens in the DWTP intake water are not completely removed by the treatment. The water used for human consumption presented mutagenic activity related to nitro-aromatics and aromatic amines compounds probably derived from the cited textile processing plant effluent discharge [G.A. Umbuzeiro, D.A. Roubicek, C.M. Rech, M.I.Z.. Sato, L.D. Claxton, Investigating the sources of the mutagenic activity found in a river using the Salmonella assay and different water extraction procedures, Chemosphere 54 (2004) 1589-1597; G.A. Umbuzeiro, H.S. Freeman, S.H. Warren, D.P. Oliveira, Y. Terao, T. Watanabe, L.D. Claxton, the contribution of azo dyes in the multagenic activity of the Cristais river, Chemosphere 60 (2005) 55-64]. Therefore, it is important to evaluate the possible risks involved in the human consumption of this contaminated water. With that objective, one sample of the cited industrial effluent was tested for carcinogenicity in the aberrant crypt foci medium-term assay in colon of Wistar rats. The rats received the effluent in natura through drinking water at concentrations of 0.1%, 1%, and 10%. The effluent mutagenicity was also confirmed in the Salmonella/microsome assay with the strains TA98 and YG1041. There was an increased number of preneoplastic lesions in the colon of rats exposed to concentrations of 1% and 10% of the effluent, and a positive response for both Salmonella strains tested. These results indicate that the discharge of the effluent should be avoided in waters used for human consumption and show the sensitivity of the ACF crypt foci assay as an important tool to evaluate the carcinogenic potential of environmental complex mixtures. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: aberrant crypt foci; azo dye; colon carcinogenesis; industrial effluent; disperse dyes; Salmonella/microsome assay